Determinan Produksi Kedelai di Indonesia dan Implikasi Kebijakannya - Kharisma, Bayu (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.07.NO.03.TAHUN 2018, 2018)
This paper aims to determine the determinants of soybean production in Indonesia and its policy implications. Based on the estimation results, the determinants affecting soybean production in Indonesia during 1984-2013 period are: harvest area, productivity, number of labor in food crop agriculture sector, soybean import of previous year and price ratio of soybean with fertilizer price. The factors that have a significant influence on soybean production are the area of harvest, productivity, the ratio of soybean prices to fertilizer prices and the amount of labor in the food crops sector. Meanwhile, various policies that can be done by the government in order to increase soybean production in Indonesia include the provision of soybean seeds, subsidized production facilities and lending, protection policies and basic price and special programs for soybean development.